2008
DOI: 10.1186/1746-160x-4-30
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of zirconia implants compared with titanium: an in vivo study

Abstract: Background: Titanium and titanium alloys are widely used for fabrication of dental implants. Since the material composition and the surface topography of a biomaterial play a fundamental role in osseointegration, various chemical and physical surface modifications have been developed to improve osseous healing. Zirconia-based implants were introduced into dental implantology as an altenative to titanium implants. Zirconia seems to be a suitable implant material because of its tooth-like colour, its mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
172
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(188 citation statements)
references
References 19 publications
7
172
0
9
Order By: Relevance
“…Its excellent biocompatibility is similar to that of titanium implants, which has been demonstrated in several animal investigations. 30 In the presented study, RAZI was modified according to the Pirker's protocol. 28 The macroretentions were limited only to the interdental space (mesial and distal part of the root) for better primary stability and osseointegration.…”
Section: Discussionmentioning
confidence: 99%
“…Its excellent biocompatibility is similar to that of titanium implants, which has been demonstrated in several animal investigations. 30 In the presented study, RAZI was modified according to the Pirker's protocol. 28 The macroretentions were limited only to the interdental space (mesial and distal part of the root) for better primary stability and osseointegration.…”
Section: Discussionmentioning
confidence: 99%
“…Their advantages include high biocompatibility (Depprich et al, 2008), good esthetic appearance (Ghazal et al, 2008), low solubility and low thermal conductivity (Chai et al, 2007). Among the crucial problems for ceramics, however, are low fracture resistance and brittleness and, consequently, no or little apparent plastic deformation can occur before fracture (Munz and Fett, 1999 j o u r n a l o f t h e m e c h a n i c a l b e h a v i o r o f b i o m e d i c a l m a t e r i a l s 5 0 ( 2 0 1 5 ) 2 0 6 -2 1 4…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-four screws type zirconia with surface modifications and twenty four titanium implants of same shape and size inserted in the tibia of minipigs a study done by Rita Depprich et al (20). The results showed that animals were normal and showed no signs of infection.…”
Section: Osseo Integrationmentioning
confidence: 90%